Preparation method and application of double-ligand Co-based metal organic framework alkaline electrolysis water catalytic electrode material
By synthesizing cobalt-based biligand MOF on nickel foam, the problem of active site regulation and poor conductivity in oxidative electrolytic water decomposition reaction is solved, and efficient and stable electrocatalytic water decomposition reaction is achieved, providing low cost electrocatalyst solution.
Patent Information
- Application Number
- CN202411558403.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-14
AI Technical Summary
In the prior art, there are problems such as difficult to regulate the active site, poor conductivity and high preparation cost in the process of oxidation electrocatalyst (OER), which limits the application of double ligand metal organic framework materials (MOFs) in the oxidation electrolytic water decomposition reaction. .
Cobalt-based biligand MOF (Co-Tdp-Bpy) was synthesized by solvothermal method on the conductive substrate foam nickel, and 2,5-diphosphonate thiophene and 4,4'-bipyridine were used as ligands to form micron flower The spherical electrocatalyst is directly used as an electrocatalytic reaction electrode, avoiding high-temperature calcination and post-treatment, and maintaining the electrode morphology and MOF structure.
Achieved a high specific surface area, good conductivity and low cost electrocatalyst, significantly improving the activity and stability of the electrocatalytic water decomposition reaction, with low overpotential and high stability, and can be used in alkaline electrolytes. Run for a long time.
Smart Images

Figure CN119307957A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy storage materials, and the technology relates to a method for preparing a metal organic framework (MOFs) material, in which a Co-based dual-ligand MOF is loaded on nickel foam to obtain a highly active and highly stable electrocatalyst. Background Art
[0002] As the problem of climate change caused by the burning of fossil fuels and human production and life continues to intensify, hydrogen energy as a high calorific value, zero-carbon renewable energy has received widespread attention. Water splitting driven by electrical energy is one of the sustainable and feasible methods for water electrolyzers to generate green and clean hydrogen energy through the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). However, the OER process involves the transfer of four electrons, which is difficult to drive in terms of reaction kinetics, restricting the development of water electrolysis technology. Therefore, the development of efficient OER electrocatalysts is crucial and urgent. Although precious metal-based catalysts, such as RuO2 and IrO2, can effectively catalyze the occurrence of OER, their scarcity and high cost hinder further development in the direction of industrialization. Transition metal-based catalysts, such as Mn, Fe, Co, Ni, Cu oxides, hydroxides and their derivatives, have the characteristics of low price and excellent activity, and have become a research hotspot in the field of OER catalysis in recent years.
[0003] Metal-organic framework materials are crystalline porous materials composed of metal nodes (clusters) and organic linking ligands through periodic combination. They were first reported by Yaghi et al. in 1995. MOF has a unique crystalline porous structure and is easy to modify and design at the molecular level. It has advantages such as clear pore structure, high specific surface area, multiple exposed active sites, uniform distribution of active sites and chemical adjustability, but it is also usually accompanied by challenges of stability and poor conductivity. To solve this problem, it can usually be modified by morphology control and preparation of composite materials. Dual-ligand MOF is a MOF material in which the metal center forms a coordination structure with two ligands at the same time. It has the following advantages: First, it can form a MOF material with multiple functional groups, which broadens the scope of application; second, it can form a unique spatial configuration, adjust the distance between metal nodes, and achieve high dispersion and full utilization of active sites; third, it can modify the coordination structure of the metal and improve the speed and mode of electron transfer. Therefore, it provides a new idea for improving mass transfer and solving the problem of poor stability, and can achieve high catalytic activity and high stability of the material. At present, the application of dual-ligand MOFs in the OER process still faces challenges such as difficulty in controlling active sites, limited conductivity, and high preparation and application costs. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the purpose of the present invention is to propose a method for preparing a metal organic framework Co-Tdp-Bpy electrocatalyst anchored by a dual ligand, which is simple to operate and has unique morphological characteristics; the cobalt-based dual ligand MOF exhibits high specific surface area, customizable chemical composition, good conductivity, low cost and other application potentials. The activity and stability of the electrocatalytic water decomposition reaction are improved.
[0005] A method for preparing a dual-ligand Co-based metal organic framework alkaline water electrolysis electrocatalytic electrode material, in which a cobalt-based MOF containing two ligands, 2,5-diphosphonothiophene and 4,4'-bipyridine, is synthesized on nickel foam in one step by a solvothermal method and directly used as an electrocatalytic reaction electrode.
[0006] The technical solution adopted by the present invention is:
[0007] A method for preparing a dual-ligand Co-based metal organic framework alkaline water electrolysis electrocatalytic electrode material, wherein a Co-Tdp-Bpy micron flower ball electrocatalyst is uniformly grown on a conductive substrate nickel foam by a solvothermal reaction, and after being alternately washed and dried with deionized water and methanol, the electrocatalyst is directly used as an electrocatalytic electrode material;
[0008] The specific steps include:
[0009] (1) Cleaning the catalyst-loaded conductive nickel foam substrate with deionized water and ethanol, and vacuum drying;
[0010] (2) Take the cleaned and dried nickel foam and cut it into a rectangular shape for later use;
[0011] (3) Add Co(NO3)3·6H2O to deionized water and stir at room temperature until completely dissolved to obtain a uniform mixed solution A; dissolve 2,5-diphosphonothiophene and 4,4'-bipyridine in methanol and stir at room temperature until completely dissolved to obtain a uniform mixed solution B; add A to B and stir until the mixture is uniform;
[0012] The concentration of Co(NO3)3·6H2O in the mixed solution is 0.01~0.1 M, the concentration of 2,5-diphosphonothiophene is 0.01~0.1 M, and the concentration of 4,4'-bipyridine is 0.01~0.1 M;
[0013] (4) Transfer the mixed solution to a Teflon-lined stainless steel autoclave, place the treated nickel foam in the autoclave at an angle, and then seal the autoclave and keep it at 100-200 °C for 24-72 hours;
[0014] (5) After the reaction is completed and the autoclave is naturally cooled, it is taken out, cleaned, and vacuum-dried to obtain an electrocatalytic material.
[0015] The electrocatalytic material is used for electrocatalytic water-oxygen separation reaction.
[0016] Furthermore, the method comprises the following specific steps:
[0017] (1) Clean the conductive nickel foam substrate with deionized water and ethanol and dry it in vacuum;
[0018] (2) Cut the nickel foam into rectangles for later use;
[0019] (3) Weigh 2,5-thiophene diphosphate (0.3-3 mmol) and 4,4'-bipyridine (0.3-3 mmol) and dissolve them in methanol solvent, stirring until they are completely dissolved;
[0020] (4) Weigh cobalt nitrate hexahydrate (Co(NO3)2·6H2O, 0.3~3 mmol) and dissolve it in deionized water. Stir until it is completely dissolved.
[0021] (5) The solutions of step (3) and step (4) are uniformly mixed and transferred to a 50 mL stainless steel autoclave lined with Teflon, and the nickel foam treated in step (2) is tilted into the autoclave. Then, the autoclave is sealed and maintained at 100-200°C for 24-72 hours;
[0022] (6) After the reaction is completed and the autoclave is naturally cooled, the nickel foam is taken out of the autoclave and repeatedly rinsed with methanol and deionized water to remove impurities and weakly adsorbed catalysts;
[0023] (7) Dry the prepared sample in a vacuum drying oven at 60 °C.
[0024] Furthermore, the nickel foam was cut into pieces with an area of 2×3 cm 2 ; Ultrasonic washing was performed with the prepared 1 M HCl, acetone, deionized water and anhydrous ethanol in sequence;
[0025] Further, 0.34 mmol of 2,5-diphosphonothiophene and 0.34 mmol of 4,4'-bipyridine were dissolved in 15 mL of methanol and stirred at room temperature for 10 min.
[0026] Further, 0.34 mmol of cobalt nitrate hexahydrate was dissolved in 15 mL of deionized water and stirred at room temperature for 10 min.
[0027] Furthermore, the high-pressure reactor was placed in an oven and heated at 120 °C for 53 h.
[0028] Furthermore, the high-pressure reactor was naturally cooled to 20°C~40°C in an oven, and after being taken out with tweezers, the prepared nickel foam catalyst was repeatedly rinsed three times on both sides with deionized water and methanol, respectively, to remove impurities and block catalysts with weak adhesion.
[0029] Furthermore, the rinsed nickel foam catalyst is placed in a vacuum drying oven for constant temperature drying for 6 to 12 hours.
[0030] Furthermore, the ultrasonic frequency of the ultrasonic equipment used is 50~53 KHz, and the stirring speed of the stirring equipment is 500 r / min.
[0031] The present invention also provides an application of the catalyst obtained by the preparation method of the above-mentioned dual-ligand Co-based metal organic framework material supported on nickel foam directly as an electrocatalyst. In a standard three-electrode system (Hg / HgO as a reference electrode, platinum wire as a counter electrode and a working electrode), the dual-ligand Co-based metal organic framework material supported on nickel foam is directly used as a working electrode and placed in an electrolyte to perform an electrocatalytic water-oxygen decomposition reaction.
[0032] Furthermore, the electrolyte described above adopts a prepared 1 M KOH solution.
[0033] The present invention adopts a hydrothermal method, uses 2,5-diphosphonic acid thiophene and 4,4'-bipyridine dual ligands to anchor the cobalt metal site, and successfully prepares the Co-Tdp-Bpy / NF material on the nickel foam substrate through a solvent thermal reaction. It does not require post-treatment such as high-temperature calcination, does not destroy the electrode morphology and MOF structure, and can be directly used as a water decomposition electrode. Compared with the prior art, the present invention has the following advantages:
[0034] 1. The dual-ligand MOF catalyst of the present invention is synthesized in one step on a conductive substrate nickel foam by a hydrothermal method to obtain a catalyst having a micron flower ball morphology, thereby avoiding the use of a binder for drop coating that affects the conductive properties and destroys the original nanostructure, and can be directly used as an electrode material without post-processing.
[0035] 2. The dual-ligand MOF catalyst described in the present invention is composed of two elements, N and O, coordinated with Co, and the electronic structure and coordination environment of Co are regulated by regulating elements such as P and S and groups containing these elements, thereby optimizing the charge transfer in the electrocatalytic process and improving the catalytic reaction activity.
[0036] 3. Electrochemical performance is an important indicator for evaluating the quality of electrocatalysts. In an alkaline 1M KOH system, Co-Tdp-Bpy / NF exhibited a high electrochemical performance at 10 mA·cm -2 and 100 mA·cm -2It has a smaller OER overpotential at a current density of 10 mA·cm, which is significantly better than other reference items; it has the smallest Tafel slope, indicating that it is the most favorable in terms of kinetics; it has the largest electrochemically active surface area, indicating that it has the most active sites; and it exhibits the smallest impedance, which accelerates the charge transfer process and the OER reaction kinetics. -2 and 100 mA·cm -2 At a current density of 1A·cm -2 At high current density, the stability can reach 160 hours.
[0037] In summary, the present invention provides a method for preparing a Co-MOF containing a dual ligand: Co-Tdp-Bpy / NF material in one step on a nickel foam substrate by a solvothermal method. The method is simple to operate, does not require post-treatment such as high-temperature calcination, and does not destroy the electrode morphology and MOF structure. The prepared material has outstanding advantages in catalyzing water decomposition reactions. In the OER process, the prepared catalyst has a lower overpotential and higher stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below.
[0039] Figure 1 X-ray diffraction patterns of the prepared Co-MOF electrocatalyst Co-Tdp-Bpy / NF and Co-Tdp-Bpy powder on the electrocatalyst surface.
[0040] Figure 2 Fourier transform infrared spectra of the prepared Co-MOF electrocatalyst Co-Tdp-Bpy / NF, ligand 2,5-diphosphonothiophene, and ligand 4,4'-bipyridine.
[0041] Figure 3 (a) is a scanning electron microscope image of Co-Tdp-Bpy powder on the surface of the prepared Co-MOF electrocatalyst; (b) is a scanning electron microscope image of the prepared Co-MOF electrocatalyst Co-Tdp-Bpy / NF.
[0042] Figure 4 This is the energy spectrum of Co-Tdp-Bpy powder on the surface of the prepared Co-MOF electrocatalyst.
[0043] Figure 5 (a) is the LSV curve of the prepared Co-MOF electrocatalyst Co-Tdp-Bpy / NF and its comparative sample; (b) is the Tafel slope of the prepared Co-MOF electrocatalyst Co-Tdp-Bpy / NF and its comparative sample.
[0044] Figure 6 (a) is the CV curve of the prepared Co-MOF electrocatalyst Co-Tdp-Bpy / NF; (b) is the electrochemically active surface area of the prepared Co-MOF electrocatalyst Co-Tdp-Bpy / NF and its comparative sample.
[0045] Figure 7 (a) shows the electrochemical impedance spectra of the prepared Co-MOF electrocatalyst Co-Tdp-Bpy / NF and its comparative sample; (b) shows the IT test of the prepared Co-MOF electrocatalyst Co-Tdp-Bpy / NF (current density is 1 A·cm -2 (c) is the it test of the prepared Co-MOF electrocatalyst Co-Tdp-Bpy / NF (current density is 10 mA·cm- 2 and 100 mA·cm -2 ) and LSV curve of the sample after test.
[0046] Figure 8 X-ray diffraction patterns of Co-Tdp-Bpy / NF before and after it test.
[0047] Fig. 9 Scanning electron microscope image of Co-Tdp-Bpy / NF after it test. DETAILED DESCRIPTION
[0048] In order to make the present invention concise and easy to understand, the following embodiments are preferred and described in detail with reference to the accompanying drawings. The raw materials mentioned above can be obtained from public commercial channels unless otherwise specified.
[0049] Example 1 Preparation of a dual-ligand Co-based metal-organic framework alkaline water electrolysis catalyst supported on nickel foam
[0050] Weigh 0.34 mmol 2,5-diphosphonothiophene and 0.34 mmol 4,4'-bipyridine into a 50 mL beaker, add 15 mL methanol, and stir at room temperature until the solid is completely dissolved to obtain solution A;
[0051] Weigh 0.34 mmol Co(NO3)2·6H2O into a 50 mL beaker, add 15 mL of deionized water and stir at room temperature until the solid is completely dissolved to obtain solution B;
[0052] Mix solution A and solution B evenly under stirring at room temperature;
[0053] The mixed solution was transferred to a 50 mL stainless steel autoclave lined with Teflon. The nickel foam was washed with deionized water and ethanol, blown dry, and cut into 2×3 cm -2 size, tilted into the kettle;
[0054] The autoclave was sealed and maintained at 120 °C for 53 h;
[0055] After the reaction is completed and the autoclave is naturally cooled to room temperature, the nickel foam is taken out of the autoclave and repeatedly rinsed with methanol and deionized water to remove impurities and weakly adsorbed catalysts;
[0056] The prepared sample was kept in a vacuum drying oven at 60° C. for 12 hours to obtain the catalyst Co-Tdp-Bpy / NF.
[0057] Comparative Example Co-Tdc-Bpy / NF
[0058] The method of Example 1 was adopted, except that the ligand 2,5-diphosphonic acid thiophene was changed to 2,5-dicarboxylic acid thiophene, and other solvent thermal conditions remained unchanged.
[0059] Comparative Example Co-Tdc / NF
[0060] The method of Example 1 was adopted, except that the ligand 4,4'-bipyridine was removed, and other solvent thermal conditions remained unchanged.
[0061] Comparative Example Co-bpy / NF
[0062] The method of Example 1 was adopted, and only the ligand 2,5-diphosphonothiophene was removed, and other solvent thermal conditions remained unchanged.
[0063] Example 2 Application of water electrolysis catalyst
[0064] The Co-Tdp-Bpy / NF catalyst in Example 1 is used for electrocatalytic water splitting OER, and the steps are as follows:
[0065] (1) Preparation of working electrode
[0066] The prepared dried Co-Tdp-Bpy / NF was cut into 1 × 1 cm 2 Directly used for working electrode;
[0067] (2) Electrocatalytic oxygen evolution reaction
[0068] All electrochemical tests were performed in a three-electrode system at room temperature, using Pt wire as the cathode, Hg / HgO electrode as the reference electrode, and the prepared catalysts and comparative samples as the anode. 1 M KOH was used as the electrolyte for the electrochemical tests. Before the electrochemical OER tests, the electrodes were activated by CV with 10 cycles and a scan rate of 50 mV·s -1 .
[0069] Example 3
[0070] (1) Characterization before Co-Tdp-Bpy / NF catalytic reaction
[0071] The prepared Co-Tdp-Bpy / NF was placed in ethanol for ultrasonic treatment to obtain the surface powder of the Co-Tdp-Bpy / NF electrocatalyst, which was applied to characterization and analysis processes such as X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), and Fourier transform infrared spectroscopy (FT-IR). Figure 1 It can be seen from the XRD diagram that the Co-Tdp-Bpy / NF catalyst synthesized in this scheme can fit well with the standard diffraction peak of Co-Tdp-Bpy obtained by crystal structure simulation, and has a slight shift toward the low diffraction angle direction, indicating the successful synthesis of Co-Tdp-Bpy on nickel foam. Figure 2 In the experiment, FT-IR tests were performed on the two ligands and MOF materials at wave numbers of 1072, 1218, 569, 731, and 989 cm -1 The peaks at 751, 1170, 1495, and 3078 cm-1 are attributed to the vibration peaks of the pyridine ring in 4,4'-bipyridine and Co-Tdp-Bpy / NF catalysts. -1 The peak at 1588 cm-1 in 4,4'-bipyridine is attributed to the peak of thiophene ring in 2,5-diphosphonothiophene and Co-tdp-bpy / NF catalyst. -1 The composite vibration peaks attributable to v(CC) and v(CN) shift to higher wavenumbers in Co-Tdp-Bpy / NF, and a new peak at 455 cm -1 The vibration peak at can be attributed to the Co-O bond, which can further prove the successful coordination of Co with 4,4'-bipyridine and 2,5-diphosphonothiophene in MOF materials.
[0072] Figure 3 The SEM images of the synthesized Co-Tdp-Bpy MOF powder and the MOF material loaded on nickel foam are shown, indicating that the Co-Tdp-Bpy powder has a nanosheet stacking structure, and the MOF material grown on the nickel foam substrate has a micron flower ball morphology. Figure 4 It shows that O, C, P, Co, N and S elements are evenly distributed.
[0073] (2) Co-Tdp-Bpy / NF electrochemical test
[0074] Electrochemical performance is an important indicator for evaluating the quality of electrocatalysts. Figure 5 The LSV shown in (a) shows that Co-Tdp-Bpy / NF has a -2 and 100 mA·cm -2The overpotentials of the two materials are 211 and 240 mV, respectively, which are significantly better than those of the reference materials (Co-Tdc-Bpy / NF, Co-Tdp / NF, and Co-Bpy / NF). In (b), Co-Tdp-Bpy / NF has the smallest Tafel slope of 29.3 mV·dec. -1 , indicating a faster OER kinetic process. Figure 6 In (b), Co-Tdp-Bpy / NF has the largest active surface area, indicating that Co-Tdp-Bpy / NF has more abundant active sites. Figure 7 In (a), it can be seen that Co-Tdp-Bpy / NF has the smallest impedance. (b) and (c) show that Co-Tdp-Bpy / NF has stability for more than 600 hours and excellent high current stability. After the stability test, the electrochemical performance did not decrease significantly, indicating that it has potential application value as an industrial hydrogen production electrocatalyst.
[0075] (3) Characterization of Co-Tdp-Bpy / NF after electrochemical testing
[0076] from Figure 8 It can be seen that after the stability test, the Co-Tdp-Bpy / NF catalyst was transformed into CoOOH species. Fig. 9 It was shown that after the reaction, the Co-Tdp-Bpy / NF catalyst could still maintain the micron-flower-like morphology, but the size increased slightly, indicating the stability of the catalyst structure.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a dual-ligand Co-based metal organic framework alkaline water electrolysis electrocatalytic electrode material, characterized in that: The Co-Tdp-Bpy micron-flower-shaped electrocatalyst was uniformly grown on the conductive substrate nickel foam by solvothermal reaction, and after being washed and dried with deionized water and methanol alternately, it was directly used as an electrocatalytic electrode material; The specific steps include: (1) Cleaning the catalyst-loaded conductive nickel foam substrate with deionized water and ethanol, and vacuum drying; (2) Dissolve 2,5-diphosphonothiophene and 4,4'-bipyridine in anhydrous methanol and stir at room temperature until they are completely dissolved to obtain a uniform mixed solution A; Take Co(NO3)3·6H2O and add it into deionized water, stir it at room temperature until it is completely dissolved, and obtain a uniform mixed solution B; Stirring solution A and solution B until they are uniformly mixed to obtain a mixed solution; The concentration of Co(NO3)3·6H2O in the mixed solution is 0.01~0.1 M, the concentration of 2,5-diphosphonothiophene is 0.01~0.1 M, and the concentration of 4,4'-bipyridine is 0.01~0.1 M; (3) Transfer the mixed solution to a stainless steel autoclave lined with Teflon, place the treated nickel foam in the autoclave at an angle, and then seal the autoclave and keep it at 100-200 °C for 24-72 hours; (4) After the reaction is completed and the autoclave is naturally cooled, the autoclave is taken out, cleaned, and vacuum dried to obtain an electrocatalytic electrode material.
2. An electrocatalytic electrode material, characterized in that: The preparation method according to claim 1 is used for preparation.
3. The use of an electrocatalytic electrode material according to claim 2, characterized in that: The electrocatalytic electrode material is used for electrocatalytic water-oxygen separation reaction.